OP0251 Bone Histology and Histomorphometry: Effects of 5 Years of Denosumab in the Freedom Study Extension. (23rd January 2014) - Brown, J. P.; Wagman, R. B.; Dempster, D. W.; Kendler, D.; Miller, P.; Bolognese, M.; Valter, I.; Beck Jensen, J.-E.; Zerbini, C.; Zanchetta, J. R.; Daizadeh, N.; Reid, I.
Abstract : Background: Denosumab (DMAb) reduces bone turnover in transiliac crest bone biopsies, which is reversible on treatment cessation (Reid JBMR 2010; Brown JBMR 2011). Long-term DMAb treatment sustains reduction in bone turnover and low incidence of vertebral and nonvertebral fractures over 6 years (Papapoulos JBMR 2012). Objectives: To evaluate the effects of DMAb on remodelling at the tissue level. Methods: The FREEDOM extension study included a transiliac crest bone biopsy substudy. Results: 13 cross-over (placebo/DMAb) and 28 long-term (DMAb/DMAb) subjects were in this substudy after 5 years of treatment. Demographics were comparable with those of the overall FREEDOM study extension population. Mean (SD) time from last DMAb dose to first tetracycline dose was 5.7 (0.5) months. Qualitative bone histology in all samples was unremarkable, showing normally mineralized lamellar bone. Of 5 subjects in the long-term group for whom osteoid could not be visualized, samples from 4 were intact and showed normal mineralization. Structural indices were similar between the cross-over and long-term groups. Resorption was decreased, as reflected by eroded surface, in both cross-over and long-term subjects vs placebo-treated subjects in FREEDOM (Table ). Double tetracycline label was seen in trabecular and/or cortical compartments in specimens from 10/13 cross-over and 14/28 long-term subjects. In 5 cross-over and 10 long-term subjects evaluable for dynamic trabecular bone parameters, dynamic remodelling indices were low in both groups, consistent with reduced bone turnover with DMAb therapy. Conclusions: DMAb treatment over 5 years results in normal bone quality with reduced bone turnover. Disclosure of Interest: J. Brown Grant/research support from: Amgen, Eli Lilly, Merck, Novartis, Pfizer, Servier, Roche, Takeda, Warner Chilcott, Consultant for: Amgen, Eli Lilly, Merck, Speakers bureau: Amgen, Eli Lilly, Merck, R. Wagman Shareholder of: Amgen, Employee of: Amgen, D. Dempster: None Declared, D. Kendler Grant/research support from: Merck, Amgen, Eli Lilly, Novartis, J&J, Roche, Pfizer, Consultant for: Merck, Amgen, Eli Lilly, Novartis, Warner Chilcott, Pfizer, Speakers bureau: Merck, Amgen, Eli Lilly, Novartis, Warner Chilcott, Pfizer, P. Miller: None Declared, M. Bolognese Grant/research support from: Lillly, Amgen, Merck, Consultant for: Lilly, Amgen, Warner-Chilcott, Speakers bureau: Lilly, Amgen, Warner-Chilcott, I. Valter: None Declared, J.-E. Beck Jensen Consultant for: Eli Lilly, Takeda Nycomed, Amgen, Novartis, MSD, Speakers bureau: Eli Lilly, Takeda Nycomed, Amgen, Novartis, MSD, C. Zerbini: None Declared, J. Zanchetta Consultant for: Amgen, Eli Lilly, Merck, GSK, Pfizer, Speakers bureau: Amgen, Eli Lilly, Merck, GSK, Pfizer, N. Daizadeh Shareholder of: Amgen, Employee of: Amgen, I. Reid: None Declared